INNOVATIVE METHODS AND TECHNOLOGIES IN EDUCATION - Khaydarova Barno Israiljanova; Ibragimova Zinnura (Galaxy International Interdisciplinary Research Journal, 2023)
Rapid changes in the socio-economic, political and cultural spheres of our country require a fundamental reform of the education system, because through an excellent education system, the young people who determine the future intellectual potential of our republic and its prosperity and development are trained every day. It plays a decisive role in education to be creative and independent. That is why it is the most important strategic direction in education and the innovative activity of educational institutions. This is an urgent issue today in all educational institutions, especially the preparation of intellectual property and the implementation of the intellectual property system in the form of innovative activities through higher education that prepares creative, high-potential specialist pedagogic personnel. Developmental goal: creative application of acquired knowledge, independent work, development of skills.